The Biological Effects of Smoking on the Formation and Rupture of Intracranial Aneurysms: A Systematic Review and Meta-Analysis - Wang, Hanbin; Wang, Luxuan; Wang, Jiyue; Zhang, Lijian; Li, Chunhui (Frontiers in Neurology, 2022)
Background: Aneurysms of the cerebral vasculature are relatively common, which grow unpredictably and even small aneurysms carry a risk of rupture. Rupture of intracranial aneurysms is a catastrophic event with a high mortality rate. Evidences have proved that smoking is extremely closely related to the formation and rupture of intracranial aneurysms. However, the biological effect caused by cigarette smoking on formation, rupture of intracranial aneurysms (IA) is still underrepresented. Methods: We searched PubMed and CNKI for all studies on smoking and intracranial aneurysms published up to December 2021, and all studies were included in the analysis. RevMan software was used for data analysis. Results: A total of 6196 patients were included in 14 original articles in this meta-analysis. The risk of ruptured IA in the current smoking group was significantly higher than that in the non-smoking group, with statistical significance (RRtotal=1.20,95%CI: 1.07 - 1.33). After heterogeneity among cohorts was removed by sensitivity analysis, there was still a statistically significant difference in the risk of ruptured IA between the smoking and non-smoking groups (RRtotal=1.29,95%CI: 1.20 - 1.39). There was no statistically significant difference in the risk of ruptured IA between the former smoking (smoking cessation) group and the non-smoking group (RRtotal=1.09,95%CI: 0.50 - 2.38). After heterogeneity among cohorts was removed by sensitivity analysis, there was still no statistically significant difference in the risk of ruptured IA between the former smoking (smoking cessation) group and non-smoking groups (RRtotal=0.75,95%CI: 0.47 - 1.19). The risk of the ruptured IA in the current smoking group was significantly higher than that in the former smoking(smoking cessation) group, with a statistically significant difference (RRtotal=1.42,95%CI: 1.27 – 1.59). Conclusions: Although the biological effects of smoking on the formation and rupture of IA are unknown, this study indicates that current smoking is a risk factor for the rupture of IA. Quitting smoking is very important for patients with IA